The Financial and Non-Financial Performance of Token-Based Crowdfunding: Certification Arbitrage, Investor Choice, and the Optimal Timing of ICOs - Niclas Dombrowski; Wolfgang Drobetz; Lars Hornuf; Paul P. Momtaz (Center for Economic Studies and ifo Institute (CESifo), 2023)
What role does the selection of an investor and the timing of financing play in initial coin offerings (ICOs)? We investigate the operating and financial performance of ventures conducting ICOs with different types of investors at different points in the ventures' life cycle. We find that, relative to purely crowdfunded ICO ventures, institutional investor-backed ICO ventures exhibit poorer operating performance and fail earlier. However, conditional on their survival, these ventures financially outperform those that do not receive institutional investor support. The diverging effects of investor backing on financial and operating performance are consistent with our theory of certification arbitrage; i.e., institutional investors use their reputation to drive up valuations and quickly exit the venture post-ICO. Our findings further indicate that there is an inverted U-shaped relationship for fundraising success of ICO ventures over their life cycle. Another inverted U-shaped relationship exists for the short-term financial performance of ICO ventures over their life cycle. Both the fundraising success and the financial performance of an ICO venture initially increase over the life cycle and eventually decrease after the product piloting stage.
Keywords: G24; G32; K22; L26; 330; Token Offering; Initial Coin Offering (ICO); crypto funds; operating versus financial performance; entrepreneurial finance; optimal timing